Power distance, uncertainty avoidance, and rukun: Managing the trans-boundary haze crisis in Indonesia - WARDOYO, Reidinar Juliane (Institutional Knowledge at Singapore Management University, 2017)
Indonesia is home to more than 200 ethnicities who speak more than 300 local languages. This chapter examines how Indonesian cultural characteristics surfaced in the face of government's crisis response in the 2013 transboundary haze crisis when forest fires that raged in Riau, Indonesia, caused the haze to spread to its neighboring countries including Singapore and Malaysia, hitting high levels of air pollution in those countries. The key to tackling the fires in Riau was for the government to determine the cause of the fires, and enforce the law by prohibiting the firms and farmers from burning the forests and peat lands. This crisis showed that the Indonesian government did not exhibit collectivist culture as it did not achieve consensus before making a decision and disseminating messages, in contrast to Hofstede's study. The 2013 transboundary haze episode pressured Indonesia to ratify the haze agreement with ratification finally occurring in September 2014.